The Language of Manipulation and Control: Operational Methods of the Securitate in A. Belc’s Film Metronom - Pavel, Ecaterina (MDPI AG, 2023)
The objective of the present study is to analyze the operational methods employed by the secret police agency (Securitate) in exerting influence and control over individuals within the Romanian communist society, as depicted in the film Metronom directed by Alexandru Belc. Through an analysis of the dialogue between the protagonist and a Securitate officer, this research explores the tactics used by the Romanian secret police to manipulate and deceive citizens, preserve power, and maintain social control. Drawing on critical discourse analysis and theories of power, this study reveals the subtle and insidious ways in which the Securitate operated within the Romanian society to silence opposition, spread propaganda, and maintain a stranglehold on society. In this line of work, a set of elements has been delineated, aimed at evaluating the manipulative nature of communist discourse strategies. The findings provide insights into the cinematic portrayal of the Securitate in Romanian communist society, highlighting the use of language and discourse as tools for controlling and manipulating both the population and individuals.
Keywords: critical discourse analysis; manipulation; power; control; Securitate; 'Metronom' film